Fairy Tales “Die Sterntaler” and Fairy Tale “Der süße Brei” on Learning German Reading Skills of Students of Grade XII-13 at SMAN 2 Sidoarjo - Febriyanti, Galuh Arzany; Dwi Imroatu Julaikah, (LATERNE, 2025)
The preliminary observation conducted with the German language teacher at SMAN 2 Sidoarjo revealed that students at SMAN 2 Sidoarjo have low learning interest in German language learning, particularly in reading skills. The students tend to show greater interest in learning media that contains numerous images within the reading texts. Therefore, in this study, fairy tales were utilized as an alternative learning medium for German language learning. The fairy tales used in this research were“Die Sterntaler” and “Der süße Brei” by the Brothers Grimm. This study aims to examine the implementation of the fairy tale media “Die Sterntaler” and “Der süße Brei” and the learning outcomes of German reading comprehension skills among students of class XII-13 at SMAN 2 Sidoarjo. The research method used in this study was descriptive qualitative. The results of this study indicate that the reading skills of students in Class XII-13 at SMAN 2 Sidoarjo have improved. This is evidenced by the observation analysis results from the first meeting, which reached a percentage of 83.33%, and from the second meeting, which reached 91.66%. Meanwhile, in terms of learning outcomes, students successfully achieved the minimum mastery criteria (KKM) in both the first and second meetings. Therefore, it can be concluded that the implementation of fairy tale media can be used as an alternative instructional medium in German language learning. Keywords: Reading Skills, Die Sterntaler Fairy Tale, Der süße Brei Fairy Tale, Learning Outcomes, German Language, German Language Learning